Mobilization of Ca2+ from Intracellular Stores in Sus scrofa domesticus Oocytes After Vitrification and Thawing - Denisenko, Vitaliy Yu.; Kuzmina, Tatiana I. (Problems of Cryobiology and Cryomedicine, 2018)
Despite a significant progress in cryopreservation of embryos and male gametes, the vitrification of animal oocytes has been still a complicated and not fully resolved task due to a high sensitivity of female gamete cell compartments to the effects of ultralow temperatures and osmotic stress. This study was aimed to identify the intracellular mechanisms, determining the cryoresistance of animal oocytes. The features of Ca2 + mobilization from intracellular stores in vitrified porcine oocytes were studied using the fluorescent probe chlortetracycline. In these cells the relationship between different intracellular Ca2+ stores (IP3 and ryanodine sensitive), provided by microfilament participation, was established to be destroyed, and that between various intracellular Ca2+ stores, formed by microtubules, underwent certain changes. The guanosine triphosphate in vitrified oocytes became incapable of forming the bond between different intracellular stores, whereas the nanoparticles of highly dispersed silica preserved it. The bond between different intracellular Ca2+ stores in the oocytes, subjected to vitrification and thawing, was established to be provided not only by microtubules, but protein kinase C as well. Probl Cryobiol Cryomed 2018; 28(2): 120-130